2022
DOI: 10.1002/gj.4577
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and magnetite mineral properties in a porphyry copper prospect in A‐type granitoids: A case study from the Karbi Hills of Northeast India

Abstract: This paper discusses the porphyry copper mineralization in A‐type granitoids from the Precambrian shield of the Karbi Hills (Mikir Hills), NE India. The prospective zone lies in the Kuthori‐Bagori of Kaziranga locality of the north Karbi Hills. The host granitoids are characterized by intermediate to high SiO2 (66.30–72.97 wt.%), Na2O (up to 4.90 wt.%), Ba (up to 1,943 ppm), Zr (up to 410 ppm), Y (up to 70 ppm) and Al2O3 (up to 14.77 wt.%) with low concentrations of CaO (up to 1.53 wt.%), and Cu (up to 32.41 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Porphyry copper mineralization in A‐type granitoids from the Precambrian shield of the Karbi Hills (Mikir Hills), north‐east India has been investigated (Majumdar, Gogoi, & Ghatak, 2022; Majumdar, Gogoi, Ghatak, Saikia, et al, 2022). It is observed that minerals in the investigated granitoids show hypogene alteration features similar to ideal porphyry‐style mineralization.…”
Section: Research Outputs Of Special Issue‐ Partmentioning
confidence: 99%
See 4 more Smart Citations
“…Porphyry copper mineralization in A‐type granitoids from the Precambrian shield of the Karbi Hills (Mikir Hills), north‐east India has been investigated (Majumdar, Gogoi, & Ghatak, 2022; Majumdar, Gogoi, Ghatak, Saikia, et al, 2022). It is observed that minerals in the investigated granitoids show hypogene alteration features similar to ideal porphyry‐style mineralization.…”
Section: Research Outputs Of Special Issue‐ Partmentioning
confidence: 99%
“…Porphyry copper mineralization in A-type granitoids from the Precambrian shield of the Karbi Hills (Mikir Hills), north-east India has been investigated Majumdar, Gogoi, Ghatak, Saikia, et al, 2022) Petrographical and geochemical characteristics of the mafic intrusives from the Naga Hills Ophiolites (NHO) have been investigated to constrain their petrogenesis and possible tectonic environment (Hussain & Dey, 2022). They suggest that the mafic intrusive rocks have an affinity to tholeiitic parental magma and are influenced by subduction zone components during their generation.…”
Section: Research Outputs Of Special Issue-partmentioning
confidence: 99%
See 3 more Smart Citations